Local order in conflict - Voyvodic Casabó, C (2021)
This thesis examines the intersections of development and security in the implementation of infrastructure projects in Colombia. The study of infrastructure in armed conflict largely focuses on its potential to deliver security through statebuilding and tends to only examine armed groups when they target infrastructure to undermine state presence in the territory. Yet, armed groups and states also cooperate, coopt, or coexist during and after internal armed conflict. Without incorporating these interactions, we lack a complete picture on how development impacts security.